Omic research in termites: an overview and a roadmap - Scharf, Michael E. (Frontiers in Genetics, 2015)
Many recent breakthroughs in our understanding of termite biology have been facilitated by “omics” research. Omic science seeks to collectively catalog, quantify and characterize pools of biological molecules that translate into structure, function and life processes of an organism. Biological molecules in this context include genomic DNA, messenger RNA, proteins and other biochemicals. Other permutations of omics that apply to termites include sociogenomics, which seeks to define social life in molecular terms (e.g., behavior, sociality, physiology, symbiosis, etc.) and digestomics, which seeks to define the collective pool of host and symbiont genes that collaborate to achieve high-efficiency lignocellulose digestion in the termite gut. This review covers a wide spectrum of termite omic studies from the past 15 years. Topics covered include a summary of terminology, the various kinds of omic efforts that have been undertaken, what has been revealed, and to a limited degree, what the results mean. Although recent omic efforts have contributed to a better understanding of many facets of termite and symbiont biology, and have created important new resources for many species, significant knowledge gaps still remain. Crossing these gaps can best be done by applying new omic resources within multi-dimensional (i.e., functional, translational and applied) research programs.